Analisis Wacana Pengaturan Cuti Haid, Hamil, Keguguran, dan Melahirkan dalam Hukum Positif Indonesia - Moeliono, Tristam Pascal; Indriyani, Oktavianti (Undang: Jurnal Hukum, 2023)
Women in the modern industrialized world are expected to satisfy quite a number of different public or country’s demands. Traditionally, as also underscored by the existing marriage law in Indonesia, they are expected to become housewives, supporting, and taking care of their husband and children. On the other hand, the modern industrial world demands them to be able handle multi task and become productive workers, to play their part as productive state’s human resources. In the face of these demands, we can discern the compromise made in the making of policies and rules in the field of labour law. This tension, as shown in conflicts and compromises made in the establishment of policies, rules, and regulations, especially in the field of labour law, granting special treatment for women labour force colours the development of special treatment policies given to women, in terms of maternity, miscarriage and menstruation leave. Those specific work leaves are made and developed based on how women’s specific nature is understood by legislators (mostly dominated by man) or based on how the masculine-economic world view perceive specific women health issues. In this article the authors grapples with legal issues stemming from the treatment of this dual function of women workers in the domestic and workspace. The existing positive law will be put under scrutiny using a discourse analysis, i.e. legal materials as discourse will be analysed using feminist critical legal theory. The authors argue the state or society’s demand to produce healthy offspring’s may well hamper the fulfilments of women’s right to work and building a professional career. Important also is how cost and benefit analysis influenced how those rights are being discussed. Abstrak Perempuan dalam dunia industri modern diharapkan dapat dan wajib memenuhi banyak harapan masyarakat dan negara. Perempuan secara tradisional dan juga secara tegas dalam hukum perkawinan Indonesia diharapkan menjadi ibu rumah tangga dan mendukung dan merawat anak-anak. Sebaliknya, dunia industri modern menuntut mereka berperan ganda dan menjadi tenaga kerja yang produktif. Berhadapan dengan dua tuntutan berbeda, kompromi dalam kebijakan dan hukum ketenagakerjaan mewarnai pengembangan kebijakan serta penetapan sejumlah perlakuan khusus bagi perempuan terkait cuti haid, keguguran, dan melahirkan. Ketiga hal itu diatur dan dikembangkan berdasarkan pemahaman pembuat undang-undang (didominasi pria) atau diwacanakan sebagai persoalan khusus kesehatan perempuan dari sudut pandang ekonomi maskulin. Tulisan ini menelaah persoalan perempuan sebagai ibu rumah tangga (ranah domestik) dan pekerja (ranah publik) dari kacamata hukum positif di Indonesia. Pendekatan yang digunakan adalah discourse analysis, di mana bahan-bahan hukum diwacanakan dengan menggunakan perspektif feminist critical legal theory. Dengan itu hendak ditunjukkan bagaimana perbincangan dan perdebatan perihal hak-hak khusus perempuan tidak dapat dipahami terlepas dari praktik-kebiasaan dunia ketenagakerjaan di Indonesia. Dari analisis yang dilakukan tampak kuatnya pengaruh cost benefit analysis serta kecemasan perihal keberlanjutan generasi penerus berkualitas dalam perbincangan hak cuti perempuan pekerja dan dukungan suami terhadap istri-pekerja.